Highly efficient antifogging and antibacterial food packaging film fabricated by novel quaternary ammonium chitosan composite. (5th March 2020) - Min, Tiantian; Zhu, Zhu; Sun, Xiaoli; Yuan, Zhipeng; Zha, Junwei; Wen, Yongqiang
Graphical abstract: Highlights: A multifunctional food packaging film with antifogging and antibacterial properties was designed. The functional film can prolong the shelf life of fruits and has broad application prospects. A simple quaternization modification enabled the coating to achieve dual functions. Chitosan is used as matrix which has good biocompatibility and biodegradability. Water is used as solvent and the progress of film preparation is green and safe. Abstract: In this work, a multifunctional food packaging composite coating with transparent, biodegradable, antifogging and antibacterial properties was designed and fabricated by quaternary ammonium salt modified chitosan (HACC) and poly (vinyl alcohol) (PVA) via a facile and environment-friendly solution casting method. A simple quaternization modification enabled the coating simultaneously to achieve excellent antifogging and antibacterial functions. The excellent antifogging property of the HACC/PVA composite coating was attributed to the strong water absorbency of quaternary ammonium chitosan and PVA. A nearly 98% transmittance ratio of coated glasses was achieved during antifogging test. In addition, the inhibition rate of the HACC/PVA composite coating kill against Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ) and Botrytis cinerea were up to 99%. The antibacterial effect was demonstrated by each group of strawberries after storage for 1, 3, 5 days. The multifunctional coating has broad prospects in the application of fruit and vegetable packaging.